English for Specific Purposes (ESP) Training for Mangrove Forest park actors to Enhance Coastal Tourism Services - Rahmiati, Rahmiati; Zulida, Evi; Fadlia, Fadlia; Altasa, Fiza Rauzika; Hasrina, Noliza (Unram Journal of Community Service, 2025)
The urgency of this PKM activity is to see the enormous tourism potential of the Mangrove Forest Park, managed by PT Perseroda (partner), and its influence on the economy of Langsa City. The increasing number of tourists at home and abroad must be accompanied by quality service and human resource capabilities. English language skills are required for all tourism operators at Mangrove Forest Park to provide quality services. Following up on this, the service team provided English for Specific Purposes (ESP) training to improve the quality of human resources' English language skills and partner services. The objectives of PKM are: (1) Improve the quality of partner human resources capabilities by improving English language communication skills specifically for Frontliners, guides, parking attendants, security and small business traders who interact directly with tourists; (2) Improving partner services through services using English to foreign tourists so that they can add value and increase the interest of foreign tourists who will visit. To achieve the objectives of this service, tests, interviews, questionnaires and observations were used to collect data. The targets for achieving this PKM activity are: (a) Increasing the ability of Partner HR in communication skills using English; (b) There has been an increase in the quality of services provided by partners which can increase the number of foreign tourists. The results of PKM activities show an increase in the ability of Partner HR to use English from a score of 55 to 75 after PKM activities. Apart from that, based on observations and interviews with participants, it is known that there has been an increase in partner services through services using English provided by frontliners and Mangrove Forest Park tour guides